Some Common Causes of Unintentional Weight Gain – A Recent Review of Literature (Journal of Food and Dietetics Research, 2023)
Weight gain is a problem that affects not only the body, but also influences people's self-esteem. This condition is often not only related to the lack of healthy habits, such as physical exercise and a balanced diet, and may have other causes, such as, thyroid problems, genetics/heredity, excess cortisol, medicines that influence appetite and metabolism etc. In addition, other factors that can influence unintentional weight gain include stress and sleep disturbances. There is scientific evidence of the role of stress as a contributing factor to weight gain. The explanation is simple and involves the body's production of hormones and enzymes that influence appetite and weight gain. Studies show, for example, that stress accelerates the production of cortisol. This hormone, in addition to slowing down metabolism, increases appetite when produced in excess. Cortisol also reinforces the desire for high-calorie foods that are high in sugar and fat, such as chips or cakes. One of the effects of stress is changes in sleep. Difficulty falling asleep, intermittent sleep and nightmares are some of the consequences that this state can have on the sleep cycle. It turns out that systematically sleeping less than 8 hours causes changes in the hormones leptin and ghrelin, responsible for controlling hunger: leptin levels (decreased appetite) decrease, while ghrelin levels (increased appetite) increase. In conclusion, other factors than diet including stress and sleep contribute to weight gain. The reverse can help in healthy weight management.
Keywords: Unintentional weight gain; Stress; Sleep; Calories; Lifestyle